Cross-class interactions and subjective inequality: perceptions, beliefs and distributive preferences at a Colombian elite university - Galeano-Salgado, Andres Mauricio; Álvarez-Rivadulla, María José (Frontiers in Sociology, 2025)
This study examines how cross-class interactions influence perceptions and beliefs of inequality, and distributive preferences. It is based on the implementation of Ser Pilo Paga, a government program that granted access to high-quality higher education for low-income students in Colombia. Drawing on 61 in-depth interviews and complementary survey data, we find that exposure to peers from different socioeconomic backgrounds recalibrates students’ understanding of inequality, making their perceptions more accurate and their attitudes toward redistribution more favorable—regardless of class. While students consistently held structural views of inequality, these interactions reshaped their views on merit, revealing its dual function as both a source of validation and a relational tool. Notably, we find that meritocratic beliefs coexisted with structural critiques, challenging assumptions that meritocracy legitimizes inequality. Finally, support for the fellowship program was nuanced and ambivalent, particularly among beneficiaries, who recognized both its benefits and its limitations as a redistributive mechanism. These findings advance sociological understandings of subjective inequality by highlighting how class contact in segregated societies can shift beliefs and preferences in ways that challenge dominant theories of self-interest and merit-based legitimation.